ABCC5, a gene that influences the anterior chamber depth, is associated with primary angle closure glaucoma - Nongpiur, M; Khor, C; Jia, H; Cornes, B; Chen, L; Qiao, C; Nair, K; Cheng, C; Xu, L; George, R; Tan, D; Abu-Amero, K; et al. (Public Library of Science, 2014)
Anterior chamber depth (ACD) is a key anatomical risk factor for primary angle closure glaucoma (PACG). We conducted a genome-wide association study (GWAS) on ACD to discover novel genes for PACG on a total of 5,308 population-based individuals of Asian descent. Genome-wide significant association was observed at a sequence variant within ABCC5 (rs1401999; per-allele effect size =  -0.045 mm, P = 8.17 × 10(-9)). This locus was associated with an increase in risk of PACG in a separate case-control study of 4,276 PACG cases and 18,801 controls (per-allele OR = 1.13 [95% CI: 1.06-1.22], P = 0.00046). The association was strengthened when a sub-group of controls with open angles were included in the analysis (per-allele OR = 1.30, P = 7.45 × 10(-9); 3,458 cases vs. 3,831 controls). Our findings suggest that the increase in PACG risk could in part be mediated by genetic sequence variants influencing anterior chamber dimensions.